2018
DOI: 10.1002/admi.201801033
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies Allow Tuning the Work Function of Vanadium Dioxide

Abstract: over a wide range by substitutional doping and external strain, etc. [3] Due to these remarkable features, VO 2 has in addition to its potential use as electrode, [4] applications such as optical switching devices, [5] memory devices, [6] and smart windows. [7] At room temperature (RT), undoped VO 2 is in the insulating state and for most VO 2 thin films the work function is moderately high (up to 5.55 eV). [8] Thus, VO 2 has not been considered as a suitable hole injecting electrode as for related hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 64 publications
1
25
1
Order By: Relevance
“…Figure 5(e) exhibits the calculated work function of VO 2 nanobeams for different hydrogen doping time. The work function of pristine VO 2 nanobeams is found to 5.39 eV, which is slightly higher than the reported value [23,43], and it decreases sequentially with increasing H-doping time. The lowest work function is found to be 5.29 eV for 10 min H doping time.…”
Section: Kelvin Probe Force Microscopycontrasting
confidence: 70%
See 1 more Smart Citation
“…Figure 5(e) exhibits the calculated work function of VO 2 nanobeams for different hydrogen doping time. The work function of pristine VO 2 nanobeams is found to 5.39 eV, which is slightly higher than the reported value [23,43], and it decreases sequentially with increasing H-doping time. The lowest work function is found to be 5.29 eV for 10 min H doping time.…”
Section: Kelvin Probe Force Microscopycontrasting
confidence: 70%
“…The lowest work function is found to be 5.29 eV for 10 min H doping time. From interpretation of the work function measured by KPFM from other recent studies, it has been found that the change in the work function is closely related to nearsurface stoichiometry (V/O ratio related to V valence) [23] or the density of point defect like oxygen vacancy in lattice [44]. In addition, the crystal structure is also considered a factor.…”
Section: Kelvin Probe Force Microscopymentioning
confidence: 97%
“…The most prominent method involves the removal of lattice oxygen atoms to form oxygen-vacant sites on the surface of the material. 14,15,[191][192][193] An alternative method to anionically-doping vanadium oxide materials is through the substitution of oxide moieties for non-oxygen anions such as halides, [194][195][196][197][198][199][200] sulfides, [201][202][203] or nitrides. 204,205 Experimental and computational investigations have shown that both physical and chemical properties are significantly influenced by the introduction of these anionic dopants.…”
Section: Anionic Dopants In Molecular Vanadium Oxide Assembliesmentioning
confidence: 99%
“…Vanadium ([Ar] 3d 3 4s 2 ) is a very reactive element and different oxides such as VO, V2O3, VO2 and V2O5 characterized by the oxidation states: V +2 , V +3 , V +4 and V +5 , respectively, can be synthetized. The WF of vanadium oxides can be tuned by changing the stoichiometry of the sample, 6,13,14 or its dimensionality. The nanoscale dimensions in thin films and nanoparticles can be an important degree of freedom to control the WF of any oxide, resulting in significant deviations of the electronic structure from that of the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…WF values of NS films and reference bulk materials taken from the literature 6,13,14,46. The extrapolated values are labelled by *.…”
mentioning
confidence: 99%